lnc-3215 Suppression Leads to Calcium Overload in Selenium Deficiency-Induced Chicken Heart Lesion via the lnc-3215-miR-1594-TNN2 Pathway - Jie Yang; Yafan Gong; Jingzeng Cai; Qi Liu; Ziwei Zhang (Molecular Therapy: Nucleic Acids, 2019)
Selenium deficiency has been proven to induce calcium disorders in the chicken heart. However, detailed regulatory mechanisms, e.g., the long noncoding RNA (lncRNA)-microRNA (miRNA)-mRNA regulatory axis, have not yet been described. Here, we point out lnc-2315, miR-1594, and Troponin T (TNNT2) based on the results of lncRNA and miRNA comparative genomics group analysis of Se-deficient chicken hearts compared with control hearts. We employed lnc-3215 and TNNT2 knockdown, miR-1594 knockdown, and overexpression models in the chicken embryos in vivo, and lnc-3215, miR-1594, and TNNT2 knockdown and overexpression models in cardiomyocytes in vitro. The dual-luciferase reporter assay and quantitative real-time PCR were used to confirm the relationships between miR-1594 and TNNT2, lnc-3215, and miR-1594 in cardiomyocytes. Our results revealed that TNNT2 suppression induced cardiac calcium overload in vivo and in vitro. miR-1594 activates cardiac calcium overload by targeting TNNT2. Moreover, we found that lnc-3215 regulates miR-1594, and thus influences the TNNT2 expression in vivo and in vitro; these conclusions were verified by gene knockdown in chicken embryos. Our present study revealed a novel regulatory model of a calcium program, which comprises lnc-3215, miR-1594, and TNNT2 in the chicken heart. Our conclusions may provide a feasible diagnostic tool for Se-deficient cardiomyocytes injury. Keywords: selenium deficiency, calcium overload, chicken heart, lnc3-215-miR1594-TNNT2 axis